Comparison of Pheromone Lures and Sticky Pad Color for Capturing Tuta absoluta (Lepidoptera: Gelechiidae) - Muhammad Sadique; Muhammad Ishtiaq; Mirza Abdul Qayyum; Wafa A. H. Alkherb; Asim Abbasi; Muhammad Arshad; Unsar Naeem Ullah; Nazar Faried; Muhammad Irfan Akram; Nazih Y. Rebouh (Insects)
Tomato leaf miner Tuta absoluta (Meyrick) (Lepidoptera: Gelechiidae) has gained the status of major pest globally. Integrated pest management (IPM) consists of different control methods. This field study was conducted to evaluate the influence of different pheromone-based traps to attract the male population and the potential of sticky pads of four different colors in capturing the adults in the absence of pheromone lures. The trials were conducted in Khyber Pakhtunkhwa (Pakistan) for two consecutive years, 2020 and 2021. The Delta trap with rubber septum type lure was significantly more attractive in both years, with mean number of capturing 76.0 and 86.17, as compared to polymer wax (32.83 and 28.2) and polymer vial (10.37 and 11.77), lures. The highest mean number of capturing of T. absoluta adults were noted as 17.93 and 21.73 with black color sticky trap without pheromone, whereas the lowest number of adults, i.e., 1.33 and 1.47, were captured during the first and second year of the study, respectively, with yellow color sticky traps. However, a significant difference was found in pheromone lures and among black, red, green, and yellow color sticky pads. Hence, Delta traps equipped with rubber septum pheromones lures and black colored sticky pads were more useful for the control of T. absoluta than any other colored sticky pads and pheromone lures alone. These findings could be helpful for the integrated management of T. absoluta.